Whole‐body vibration for improving function after stroke - Chang, Xueli (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and safety of WBV therapy for improving activities of daily living and qualify of life in people with stroke.